2015
DOI: 10.1111/bph.13250
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol is a negative allosteric modulator of the cannabinoid CB1 receptor

Abstract: BACKGROUND AND PURPOSECannabidiol has been reported to act as an antagonist at cannabinoid CB 1 receptors. We hypothesized that cannabidiol would inhibit cannabinoid agonist activity through negative allosteric modulation of CB 1 receptors. EXPERIMENTAL APPROACHInternalization of CB 1 receptors, arrestin2 recruitment, and PLCβ3 and ERK1/2 phosphorylation, were quantified in HEK 293A cells heterologously expressing CB 1 receptors and in the STHdh Q7/Q7 cell model of striatal neurons endogenously expressing CB 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
575
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 816 publications
(642 citation statements)
references
References 48 publications
(135 reference statements)
20
575
2
8
Order By: Relevance
“…37 Understanding the mechanism by which CBD partially ameliorates THC's effects may provide insight into why this effect is not as robust as expected. Recent in vitro evidence suggests that CBD may inhibit the effects of THC through negative allosteric modulation of the CB 1 receptor, 38 whereas human neuroimaging studies indicate that THC and CBD differentially influence brain activity while performing cognitive or emotional tasks. [39][40][41] And while both additive 36 and antagonistic 18,42 associations have been reported between these agents in rodents, to date no studies have provided a direct mechanism as to how CBD moderates THC's behavioural effects.…”
Section: Discussionmentioning
confidence: 99%
“…37 Understanding the mechanism by which CBD partially ameliorates THC's effects may provide insight into why this effect is not as robust as expected. Recent in vitro evidence suggests that CBD may inhibit the effects of THC through negative allosteric modulation of the CB 1 receptor, 38 whereas human neuroimaging studies indicate that THC and CBD differentially influence brain activity while performing cognitive or emotional tasks. [39][40][41] And while both additive 36 and antagonistic 18,42 associations have been reported between these agents in rodents, to date no studies have provided a direct mechanism as to how CBD moderates THC's behavioural effects.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse vas deferens experiments showed that CBD produces weak antagonism of CB1 receptor agonists (IC 50 ϭ 3.35 M) (680). A recent study, yet to be confirmed by further investigations, points to CBD as a negative allosteric modulator of CB1 (454).…”
Section: Introduction: Cannabis and Cannabinoids Ancient Drugs Bementioning
confidence: 96%
“…In addition, CBD is a very potent anti-oxidant, more protective than α-tocopherol or vitamin C [16]. On CB1 receptors, CBD acts as negative allosterical modulator, decreasing partially the activity of ligands [17]. On CB2 receptors, CBD can act as receptor-inverse agonist.…”
Section: Resultsmentioning
confidence: 99%